Tiktok popularity one of the powerhouse in online business startup / Muhammad Adib Izudin Mohamed Rashidi … [et al.] - Mohamed Rashidi, Muhammad Adib Izudin; Sallehen, Mia Nur Maisara; Khairul Anwar, Khairul Ikhwan; Noor Azarul, Muhammad Danial; Alizan, Siti Nur Nabilah; Ibrahim, Noor Afzaliza Nazira (Faculty of Communication & Media Studies, 2023)
Social media is becoming a crucial element that helps people not only in terms of entertainment and education, but also in the business world. In order to increase business growth, these businesses will continuously look for new methods to use existing platforms into their marketing strategies. TikTok is one of the social media platforms where many marketers have ventured. It is crucial for businesses to market their products globally. The availability of social media can help these businesses in achieving their objectives for business expansion. The purpose of this research is to further understand TikTok’s impact on the business sector even in the presence of other social media. This study conducts a comprehensive literature search using a systematic review methodology and also screening study abstracts. The findings indicate that using TikTok as a mediator between businesses and consumers requires more work in storytelling, entering into real-world connections with consumers, and evolving with the customers to be social and human with trust. In addition, the researchers also found that using TikTok Apps is highly effective in creating two-way conversation.